Analisis Kedisiplinan Siswa SMK Darul Mukhlisin Dengan Pendekatan Manajemen Konflik Di Kabupaten Jember - Achtiar, Rani; Rahmah, Sovi Amalia; Putri, Amitya Anggita; Fitriana, Aniqotuzzuhro’ (CV. ITTC INDONESIA, 2022)
The character of discipline is crucial in supporting the process of education. However, some students at SMK Darul Mukhlisin still do not exhibit disciplined behavior, which can have negative effects on themselves, such as punishment. The purpose of this study is to evaluate the level of learning discipline among 12th-grade students at SMK in Jember Regency, using a qualitative approach with a descriptive method. The data collection techniques used were interviews with the head of the SMK school, the homeroom teacher of the 12th grade at SMK, and 6 students from the 12th grade at SMK, as well as observation and documentation. Based on the research results, some students show a lack of undisciplined behavior. However, the undisciplined students are aware of their mistakes. This study highlights several aspects of learning discipline, such as student attendance in class, where there are still students who frequently absent or are absent without clear reasons or explanations. In addition, some students also pay less attention to their attire, such as school uniform, which gives the impression that they are not neat when wearing clothes at school. Among the 6 respondents, their conflict resolution style can be seen from the conflict management approach. Four respondents belong to the fox style, while two respondents belong to the owl style.